p38 regulates the tumor suppressor PDCD4 via the TSC-mTORC1 pathway - Clarissa Braun; Karl Katholnig; Christopher Kaltenecker; Monika Linke; Nyamdelger Sukhbaatar; Markus Hengstschläger; Thomas Weichhart (Cell Stress, 2021)
Programmed cell death protein 4 (PDCD4) exerts critical functions as tumor suppressor and in immune cells to regulate inflammatory pro-cesses. The phosphoinositide 3-kinase (PI3K) promotes degradation of PDCD4 via mammalian target of rapamycin complex 1 (mTORC1). How-ever, additional pathways that may regulate PDCD4 expression are largely ill-defined. In this study, we have found that activation of the mitogen-activated protein kinase p38 promoted degradation of PDCD4 in macrophages and fibroblasts. Mechanistically, we identified a path-way from p38 and its substrate MAP kinase-activated protein kinase 2 (MK2) to the tuberous sclerosis complex (TSC) to regulate mTORC1-dependent degradation of PDCD4. Moreover, we provide evidence that TSC1 and TSC2 regulate PDCD4 expression via an additional mechanism independent of mTORC1. These novel data extend our knowledge of how PDCD4 expression is regulated by stress- and nutrient-sensing pathways.